Nasal/buccal midazolam use in the community. Issue 1 (7th January 2004) - Wilson, M T; Macleod, S; O'Regan, M E
Abstract : A telephone survey was carried out to evaluate the effectiveness and convenience of nasal/buccal midazolam in terminating prolonged seizures in the community. A total of 33/40 (83%) families who had used it found it effective and easy to use; 20/24 (83%) preferred using midazolam to rectal diazepam.